Brunner's gland hyperplasia in a geriatric chimpanzee (Pan troglodytes), an infrequently reported lesion. Issue 6 (25th June 2020) - Walker, David; Arends, Mark J.; Morrison, Linda R.
Abstract: Benign duodenal tumours have very rarely been reported in captive non‐human primates and are also rare in human beings. Brunner's gland hyperplasia has not been fully described in a non‐human primate. Here, we report Brunner's gland hyperplasia in a geriatric chimpanzee, which was an incidental finding during post‐mortem examination.